2010
DOI: 10.1159/000324012
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Inhibits miR-1 Expression through p38 MAPK Signal Pathway in Post-infarction Rat Cardiomyocytes

Abstract: Tanshinone IIA is a fat-soluble pharmacologically active ingredient of Danshen, a well-known traditional Chinese medicine used for cardiovascular diseases such as coronary heart disease. Tanshinone IIA has been confirmed to suppress miR-1 and reduce the arrhythmogenesis after myocardial infarction (MI). However, the modulation mechanism is not clear. Tanshinone IIA was administrated daily for 7 days before ligation of the left anterior descending artery (LAD) and lasted for 3 months after LAD. Neonatal cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 33 publications
4
71
0
Order By: Relevance
“…Moreover, propranolol inhibited the beta-adrenoceptor-cAMP-PKA signaling pathway and suppressed SRF expression and partially produced beneficial effects by down-regulating [40]. Furthermore, Tanshinone IIA could inhibit miR-1 expression by inhibiting activated p38 MAPK and heart special transcription factors, SRF and MEF2, in ischemic and hypoxic cardiomyocytes [41]. Therefore, miR-1 was a key molecule in the development of ventricular arrhythmias, which was emphasized in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, propranolol inhibited the beta-adrenoceptor-cAMP-PKA signaling pathway and suppressed SRF expression and partially produced beneficial effects by down-regulating [40]. Furthermore, Tanshinone IIA could inhibit miR-1 expression by inhibiting activated p38 MAPK and heart special transcription factors, SRF and MEF2, in ischemic and hypoxic cardiomyocytes [41]. Therefore, miR-1 was a key molecule in the development of ventricular arrhythmias, which was emphasized in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…Undoubtedly all these data supported that the structural and functional protection of LBPs on Tg mouse hearts was due largely to the down‐regulation of miR‐1 level and subsequent restoration of target proteins essential for cardiac contractile function. Other studies found that tanshinone IIA, an active component of a traditional Chinese medicine based on Salvia Miltiorrhiza, protected against arrhythmogenesis after myocardial infarction and cardiac sudden death induced by lethal arrhythmias via repression of miR‐1,8, 13 and Propranolol exerted ischaemic cardioprotection related to down‐regulation of miR‐1,7 providing powerful supports for our cardioprotective result of LBPs on HF by down‐regulation of miR‐1. These findings not only help us understand the mechanisms underlying the beneficial effects of LBPs on HF, but also conceptually advance our view regarding miRNAs to serve as potential therapeutic drug targets.…”
Section: Discussionmentioning
confidence: 71%
“…Tanshinone ⅡA was shown to relieve ischemia-induced injury, decrease the elevated miR-1 levels in ischemic and hypoxic cardiomyocytes, and consequently restored the normal level of the miR-1 target Cx43. In ischemic and hypoxic cardiomyocytes, tanshinone ⅡA also inhibited activated p38 MAPK, SRF and MEF2 [92] .…”
Section: Therapeutic Opportunitiesmentioning
confidence: 92%